A2A adenosine receptors and Parkinson's disease severity. (30th August 2013) - Casetta, I.; Vincenzi, F.; Bencivelli, D.; Corciulo, C.; Gentile, M.; Granieri, E.; Borea, P.A.; Varani, K.
<x xml:space="preserve">Abstract</x> Objectives In the last decade, increasing evidence suggests a key role of adenosine in Parkinson's disease (PD) and A2A adenosine receptors (A2AARs) as an important pharmacological target in PD. An overexpression of A2AARs has been found in putamen and in peripheral blood cells of PD patients. The primary aim of this study was to verify whether the alterations in A2AARs in lymphocytes of PD subjects correlate with disease severity. Material and methods A consecutive sample of PD patients was enrolled. A clinical examination and a face‐to‐face interview were carried out. A2AARs were investigated to verify the affinity and receptor density in lymphocyte membranes. The data were compared with those found in healthy controls. Moreover, the correlation between A2AAR density and affinity and clinical variables was evaluated in PD patients. Results In human lymphocyte membranes from PD patients, an increase in A2AAR density and a decrease in A2AAR affinity were found if compared with healthy subjects. A statistically significant correlation between the A2AAR density or affinity and specific clinical parameters as motor and cognitive impairment was detected. Patients with higher A2AAR density and lower affinity were more likely to exhibit motor complications. Conclusions Parkinson's disease patients show an A2AAR upregulation in lymphocyte membranes if compared with healthy subjects. The correlation found between A2AAR density or affinity and clinical parameters highlights the central role of A2AAR modulation in the pharmacological treatment for PD and could suggest the putative role of A2AAR as a candidate biomarker of PD severity.